Antidepressant-like effects of the Radix Bupleuri and Radix Paeoniae Alba drug pair. (28th October 2016) - Wang, Ying; Gao, Shu-Ming; Li, Ran; Zhang, Min; Gao, Shan; Yu, Chun-Quan
Highlights: The drug pair composed of Radix Bupleuri and Radix Paeoniae Alba lessens immobility time in animal behavior experiments. The drug pair composed of Radix Bupleuri and Radix Paeoniae Alba is able to antagonize hypothermia induced by reserpine in mice. The drug pair composed of Radix Bupleuri and Radix Paeoniae Alba elevates the concentrations of 5-HT and NE in hippocampal and cortical tissues. Abstract: The Radix Bupleuri and Radix Paeoniae Alba drug pair plays a pivotal role in Xiaoyaosan, a famous Chinese herbal preparation that is popular in clinical medicine. To investigate the antidepressant-like effects and potential mechanism of action of the Radix Bupleuri and Radix Paeoniae Alba drug pair, we carried out the forced swim test (FST) and tail suspension test (TST), as the mouse models of depression; and the open field test (OFT) to exclude false-positive results. Subsequently, ptosis and hypothermia induced by reserpine were assessed. Finally, the concentrations of monoamine neurotransmitters and their metabolites, namely epinephrine (NE), 5-hydroxytryptamine (5-HT), and 5-hydroxyindoleacetic acid (5-HIAA) in the hippocampal and cortical tissues of mice were detected with HPLC with electrochemical detector. The Radix Bupleuri and Radix Paeoniae Alba (1:1) drug pair at low, medium, and high doses decreased immobility time in both the FST and TST, and counteracted hypothermia induced by reserpine in mice. After the administration of reserpine, the concentrations of 5-HT and NE in the hippocampal and cortical tissues were decreased; however, pre-treatment with the Radix Bupleuri and Radix Paeoniae Alba drug pair significantly elevated the concentrations of 5-HT and NE in the hippocampal and cortical tissues. The results suggested that, compared with single dose of fluoxetine and the drugs used individually, the Radix Bupleuri and Radix Paeoniae Alba drug pair had an excellent antidepressant-like effect. These data revealed a possible mechanism of action, as the regulation of the central monoaminergic neurotransmitter system in the hippocampal and cortical tissues.